Free Radicals: Making a Case for Battery Modeling. (December 2020) - Howey, David A.; Roberts, Scott A.; Viswanathan, Venkatasubramanian; Mistry, Aashutosh; Beuse, Martin; Khoo, Edwin; DeCaluwe, Steven C.; Sulzer, Valentin
Abstract : Mathematical modeling to understand battery performance has a history of more than 50 years. The essence of modeling is to make predictions, as is the case across all scientific disciplines; indeed, we can think of models as hypotheses or theories to be tested against experimental data. Models allow us to interpolate between and extrapolate from points in data; without them, a new experiment would need to be run for every use case of a battery.